ABBV744 as a potential inhibitor of SARSCoV2 main protease enzyme against COVID19 - Zeynab Fakhar; Shama Khan; Afrah Alkhuriji; Suliman Y. AlOmar; Aijaz Ahmad (Nature Research, 2023)
A new pathogen severe acute respiratory syndrome coronavirus 2 (SARS‑CoV‑2) has spread worldwide and become pandemic with thousands new deaths and infected cases globally. To address coronavirus disease (COVID‑19), currently no effective drug or vaccine is available. This necessity motivated us to explore potential lead compounds by considering drug repurposing approach targeting main protease (Mpro) enzyme of SARS‑CoV‑2. This enzyme considered to be an attractive drug target as it contributes significantly in mediating viral replication and transcription. Herein, comprehensive computational investigations were performed to identify potential inhibitors of SARS‑CoV‑2 Mpro enzyme. The structure‑based pharmacophore modeling was developed based on the co‑crystallized structure of the enzyme with its biological active inhibitor. The generated hypotheses were applied for virtual screening based PhaseScore. Docking based virtual screening workflow was used to generate hit compounds using HTVS, SP and XP based Glide GScore. The pharmacological and physicochemical properties of the selected lead compounds were characterized using ADMET. Molecular dynamics simulations were performed to explore the binding affinities of the considered lead compounds. Binding energies revealed that compound ABBV‑744 binds to the Mpro with strong affinity (ΔGbind −45.43 kcal/mol), and the complex is more stable in comparison with other protein–ligand complexes. Our study classified three best compounds which could be considered as promising inhibitors against main protease SARS‑CoV‑2 virus